2021
DOI: 10.5851/kosfa.2021.e11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Probiotic Characteristics of Newly Isolated Lactic Acid Bacteria from Dry-Aged Hanwoo Beef

Abstract: Upload this completed form to website with submission ARTICLE INFORMATION Fill in information in each box belowArticle Title Evaluation of probiotic characteristics of newly isolated lactic acid bacteria from dry-aged Hanwoo beef Running Title (within 10 words)Lactic acid bacteria from dry-aged beef

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Kim et al . (2021) conducted a study where beef was dry‐aged at temperatures ranging from 1 to 4 °C and relative humidity between 80% and 90% for 50 days. They observed that lactic acid bacteria exhibited the highest abundance (>40%) among the bacterial populations present in dry‐aged beef, a finding consistent with our results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al . (2021) conducted a study where beef was dry‐aged at temperatures ranging from 1 to 4 °C and relative humidity between 80% and 90% for 50 days. They observed that lactic acid bacteria exhibited the highest abundance (>40%) among the bacterial populations present in dry‐aged beef, a finding consistent with our results.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to their acid-producing capabilities, lactic acid bacteria also possess robust protease and lipase hydrolysis activities, leading to the production of peptides, free amino acids, and free fatty acids, all of which contribute to enhancing the flavour of beef. Kim et al (2021) conducted a study where beef was dry-aged at temperatures ranging from 1 to 4 °C and relative humidity between 80% and 90% for 50 days. They observed that lactic acid bacteria exhibited the highest abundance (>40%) among the bacterial populations present in dry-aged beef, a finding consistent with our results.…”
Section: Analysis Of Community Composition At the Phylum Levelmentioning
confidence: 99%
“…LGG is often used as a positive control in these studies because it has been reported to colonize well in the C. elegans gut and adhere to mucins (both in vitro and in vivo), which could constitute an important mechanism for probiotics. Indeed, increased colonization of Lactobacillus sakei 20D49 [ 77 ], L. fermentum JDFM216 [ 65 , 78 ], Lacticaseibacillus rhamnosus GG [ 79 ], Lacticaseibacillus rhamnosus Probio-M9 [ 80 ], Lactobacillus spp. Lb21 [ 71 ], and multiple strains of L. salivarius and L. plantarum [ 41 , 63 ] in the worm gut was associated with improved lifespan and/or resistance to enteropathogens like E. faecalis , S. aureus , E. coli O157:H7, C. jejuni , S. typhimurium , and MRSA.…”
Section: Geroprotective Effects Of Probiotics In C Elegansmentioning
confidence: 99%
“…However, in the case of CPCC 101271, although it improved lifespan by approximately 40% compared to OP50, B. nematocida outcompeted it and induced microbiota dysbiosis (according to metagenomic sequencing) [ 81 ]. Interestingly, despite Enterococcus being a source of infection in many models, multiple E. faecalis strains (12D26, 20D48, and 30D36) also have been suggested as potential probiotics as they enhanced resistance to E. coli O157:H7 and S. aureus , likely due to significant adhesion to mucin proteins and colonization in the C. elegans gut [ 77 ].…”
Section: Geroprotective Effects Of Probiotics In C Elegansmentioning
confidence: 99%
“…The antimicrobial activity of L. https://doi.org/10.11002/kjfp.2022.29.6.852 (Abitayeva et al, 2021;Costa et al, 2020), Vibrio sp. (Joffraud et al, 2006), S. aureus, Serratia marcescens, E. coli (Abitayeva et al, 2021), and Salmonella typhimurium SL1344 (Kim et al, 2021), Huh and Hwang (2016) reported that L. sakei subsp.…”
Section: Antimicrobial Activity Of L Sakei Under Selective Environmen...mentioning
confidence: 99%